Rethinking Moundville and Its Hinterland - Scarry, C. Margaret; Steponaitis, Vincas P. (Book collections on Project MUSE., 2016)
"The Moundville archaeological site, located in Alabama, is well-known as a prime example of a Mississippian mound complex. Building upon the 1998 volume 'Archaeology of the Moundville Chiefdom, ' this volume closes the information gap and presents the results of ongoing and multifaceted research into the life of the people of the Moundville chiefdom"--Provided by publisher.